Chaetomitrium Perarmatum - Monica Suleiman; Hiroyuki Akiyama (2014)
(1) Plants are simple or sparingly branched, gradually tapering, and slightly flattened; (2) branch leaves are moderately lax, deeply concave, with mucronate apices; (3) leaf margins are widely incurved on one side, coarsely dentate above and denticulate to the base with simple teeth; (4) costae are strong; (5) lamina cells are coarsely spinose above, occasionally tuberculate, to 14 μm in diameter, and strongly prorate to the base; (6) setae are 9 mm long, setulose, and papillose at the extreme base; (7) capsules inclined, smooth and widest below mouth; (8) calyptrae cucullate, hispid all over surface, gradually short and sparse towards the base, base naked but with a few short hairs.